Peningkatan Tren Minat Beli Produk Kosmetik yang Dipengaruhi oleh Digital Marketing - Trisna, Anisya Bella; Yusuf, Budi Permana (Jurnal Ecogen, 2024)
In order to increase economic growth, a country needs to strengthen the MSME sector, one of the ways is by transforming into the digital world. Digital marketing is currently important for the business world. Because digital marketing can increase buying interest easily, on target and cost-effectively. The purpose of this study is to show the impact of using digital marketing on buying interest in Azarine products using quantitative research. A sample of 92 respondents was taken using purposive sampling technique. Respondents in this study were MAN students in Cibinong sub-district. The results showed that there was an effect of digital marketing on social media on buying interest in Azarine products by 64.8%.